ENHANCING GROWTH PERFORMANCE, ANTIOXIDANT DEFENSE, AND IMMUNE RESPONSE IN STRIPED CATFISH (Pangasius hypophthalmus) THROUGH DIETARY SUPPLEMENTATION WITH Aloe vera: A SUSTAINABLE AQUACULTURE APPROACH - Fazal, Rana Mehroz; Fatima, Arooj; Al Sulivany, Basim. S. A.; Hussain, Rashid; Hassan, Ali; Shahid, Ayesha; Ashiq, Kiran; Owais, Muhammad (Science Journal of University of Zakho, 2025)
A 60-day feeding trial was conducted to investigate the effects of dietary Aloe vera leaf powder supplementation on growth performance, hematological parameters, antioxidant status, and immune responses in Pangasius hypophthalmus. A total of 300 juvenile striped catfish with an initial weight of 14.2±0.13 g was randomly allocated to five dietary treatments containing 0% (control), 0.5%, 1%, 2%, and 4% Aloe vera leaf powder, with three replicates per group. Results reveal significant dose-dependent enhancements in growth parameters, with the 2% Aloe vera group exhibiting the highest final weight 72.21±1.54 g, weight gain 371.1±4.5%, and specific growth rate (3.21 ± 0.03%/day), alongside the lowest feed conversion ratio (1.54 ± 0.01) (p<0.05). Hematological analysis revealed enhanced red blood cell count (2.32±0.06 ×10⁶/μL), hemoglobin levels (9.0±0.3 g/dL), and white blood cell count (66.5±2.1 ×10³/μL) in the 2% group. Antioxidant enzyme activities (Superoxide dismutase (SOD), Catalase (CAT), and Glutathione peroxidase (GPx)) increased by 52.1%, 36.2%, and 27.8%, respectively, while malondialdehyde levels decreased by 31.8% related to the (control; p<0.05). Immune parameters were also significantly elevated, including lysozyme activity (14.3±0.5 U/mL) and phagocytic index (33.87±1.3%). These findings indicate that 2% Aloe vera supplementation optimally enhances growth, physiological resilience, and disease resistance in P. hypophthalmus, offering a sustainable alternative to synthetic additives in aquaculture